Refleksi Nilai Pendidikan Karakter dalam Cerita Rakyat Abu Nawir - Nofrahadi, Nofrahadi; Rafdisyam, Rafdisyam; Mohamad, Hafrison; Eka Amelia, Rezky; Sohnui, Suhailee (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
The purpose of this study is to identify and interpret the values of character education in a folklore entitled Abu Nawir. Character education is an effort to help the growth and development of the inner and outer souls of the younger generation from their innate characteristics towards a society full of compassion. Reflections of character education values contained in folklore are used as